2014
DOI: 10.1007/s00244-014-0095-6
|View full text |Cite
|
Sign up to set email alerts
|

Author’s Response

Abstract: This letter to the editor rebuts flawed analyses made by O'Reilly (2014) and points out duplicative comments that have already been rebutted in the peer-reviewed literature. O'Reilly (2014) provides little new scientific information on the source apportionment of polycyclic aromatic hydrocarbons (PAHs) in sediments, and the author stands by the results of her research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In Mahler et al 2005 suggested that RCTS could be an important source of PAHs to some urban sediments. Although, the relative contribution of PAHs from RTCS to urban sediments has been the subject of debate (DeMott and Gauthier 2006;Van Metre et al 2009;DeMott et al 2010;Van Metre and Mahler 2010;O'Reilly et al 2012O'Reilly et al , 2014O'Reilly et al , 2015Crane 2014aCrane , 2014bGauthier and DeMott 2014;O'Reilly and Ahn 2017), concern regarding the potential for exposure of aquatic organisms to PAHs specifically derived from pavement sealers has continued (Mahler et al 2012;USGS 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Mahler et al 2005 suggested that RCTS could be an important source of PAHs to some urban sediments. Although, the relative contribution of PAHs from RTCS to urban sediments has been the subject of debate (DeMott and Gauthier 2006;Van Metre et al 2009;DeMott et al 2010;Van Metre and Mahler 2010;O'Reilly et al 2012O'Reilly et al , 2014O'Reilly et al , 2015Crane 2014aCrane , 2014bGauthier and DeMott 2014;O'Reilly and Ahn 2017), concern regarding the potential for exposure of aquatic organisms to PAHs specifically derived from pavement sealers has continued (Mahler et al 2012;USGS 2016).…”
Section: Introductionmentioning
confidence: 99%